2022
DOI: 10.1101/2022.03.21.22272480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered microRNA expression in severe COVID-19: potential prognostic and pathophysiological role

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is ongoing. The pathophysiology of SARS-CoV-2 infection is beginning to be elucidated but the role of microRNAs (miRNAs), small non-coding RNAs that regulate gene expression, remains incompletely understood. They play a role in the pathophysiology of viral infections with potential use as biomarkers. The objective of this study was to identify miRNAs as biomarkers of severe COVID-19 and to analyze their role in the pathophysio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 87 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…Recent studies have suggested that circulating miRNAs hold promise as biomarkers for identifying COVID-19 cases (1,3,19,20). Among various miRNAs, miR-200b-3p and miR-214-3p specifically bind to the 3' untranslated regions (UTRs) of ACE2 and TMPRSS2 mRNAs, respectively, leading to the dysregulation of ACE2 and TMPRSS2 expression (19,(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Recent studies have suggested that circulating miRNAs hold promise as biomarkers for identifying COVID-19 cases (1,3,19,20). Among various miRNAs, miR-200b-3p and miR-214-3p specifically bind to the 3' untranslated regions (UTRs) of ACE2 and TMPRSS2 mRNAs, respectively, leading to the dysregulation of ACE2 and TMPRSS2 expression (19,(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%